RADICALISM, EXTREMISM, AND TERRORISM – THE ENEMIES OF SUSTAINABLE DEVELOPMENT (Web of Teachers: Inderscience Research, 2025)
This article discusses one of the major global challenges faced by the world community today – radicalism, extremism and terrorism. It examines the origins and consequences of these destructive ideologies, their obstruction to human development, and the need for collective effors to eradicate such malevolent and fanatical movements. It is emphasized that radicalism, extremism and terrorism are among the greatest factors hindering the progress of the New Uzbekistan in the 21st century.